Technology friendly industrial policy: international experiences and suggestions for Vietnam - Tuyen, Hoang Van; Nga, Nguyen Thi Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Industrial policies are important for industrial development process of many nations in the world. Industrial policies once effective would push up the growth of economy, produce high quality products and enhance competitiveness and position of enterprises. On basis of analysis of experiences from some countries on matter of technology friendly industrial policies as well as development of resources and infrastructure for this model, the paper proposes certain suggestions for Vietnam in the time to come for issuance of adequate industrial policies and for contribution to accelerate the industrialization-modernization of the country. Code: 19031801